PHOTOCATALYTIC CONVERSION OF CO2 TO METHANOL USING CUO-ZNO Z-SCHEME HETEROJUNCTION PHOTOCATALYST FROM ZNC BATTERY WASTE - Khansa Ibrahim, Jilan
Carbon dioxide (CO2) as the main contributor of anthropogenic greenhouse gas emissions creates an urgency in developing a solution in mitigating the excess release of carbon into the atmosphere and preventing the ever-worsening climate change. A photocatalytic process of converting CO2 into methanol using ZnO-CuO z-scheme nanocomposite photocatalyst is proven to be effective with usage of battery waste. The ZnO-CuO nanocomposites with several loading variations of 2.5, 5, 7.5, and 10 %-mol were successfully synthesized through a co-precipitation method. The ZnO photocatalyst from ZnC battery waste was also successfully synthesized using hydrometallurgical method. An optimum loading of the battery waste-based catalyst was also synthesized at 5%-mol according to photocatalyst characterization results. XRD analysis shows a successful formation of all photocatalysts with a crystal structure analysis due to peak shifts, crystallinity, and average crystalline sizes. SEM results showed the morphological changes of the photocatalyst in respect to the loading. UV-Vis DRS displays an increased absorbance in the visible light region wavelength and decreased band-gap in respect towards CuO loading increase. The visible light region absorbance of the ZnO photocatalyst created from battery waste was proven to be higher than the commercial precursor. N2 Isotherm (BET-BJH method) was able to ascertain that all photocatalysts are mesopores with H3 hysteresis type with varying surface area, pore volume, pore diameter, and pore size distribution. The activity test has shown that compared to all photocatalysts variation, the 5% CuO-ZnO from battery waste has the highest methanol yield. The high production rate and kinetics can be analyzed statistically, the suggested scheme is a z-scheme mechanism. The 2-way interaction of the pH of the environment and loading of the ZnO, also both pH and loading independently affects the methanol production by photocatalytic conversion while the source of the photocatalyst does not (i.e. battery or commercial), this leads to the conclusion that battery waste based photocatalyst may produce comparable results or even better.